2020
DOI: 10.1111/arcm.12598
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of small fragments of metals from Castillo de Huarmey (Peru): Chemical analysis in the micro‐area using FE‐SEM‐EDS, FE‐EMPA and XRD

Abstract: Small metal fragments were found in the tomb of the Wari culture elite (Castillo de Huarmey, Peru). These objects were subjected to chemical analysis using a scanning electron microscope with energy‐dispersive X‐ray spectroscopy and field emission (FE‐SEM‐EDS), an electron microprobe analyser with field emission (FE‐EMPA) and X‐ray diffraction (XRD) analysis. Chemical composition analysis showed that four different alloys were used to make copper objects. Two different alloys were found in silver alloys. A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The values are close to δ 109 Ag = 0 and literature data (Arribas et al, 2020; Mathur et al, 2018) show that the values of δ 109 Ag for sulphide and native Ag ores are in the range −0.4 to 0.4‰ for hypogenic ore and supergenic ores of native Ag. Kałaska et al (2020), describing the chemical data obtained during chemical analysis in the micro‐area of the same samples, initially described the chemical composition of the ores used in the production of individual samples. However, he was unable to determine whether primary or secondary ores were used, but only the phase chemistry of the remaining alloy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The values are close to δ 109 Ag = 0 and literature data (Arribas et al, 2020; Mathur et al, 2018) show that the values of δ 109 Ag for sulphide and native Ag ores are in the range −0.4 to 0.4‰ for hypogenic ore and supergenic ores of native Ag. Kałaska et al (2020), describing the chemical data obtained during chemical analysis in the micro‐area of the same samples, initially described the chemical composition of the ores used in the production of individual samples. However, he was unable to determine whether primary or secondary ores were used, but only the phase chemistry of the remaining alloy.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation of the MK 33 sample with the samples from the Tiwanaku artefacts is also visible (Figure 6a). Kałaska et al (2020) showed that the MK 33 sample had a distinct composition of inclusions in the alloy compared to other samples. It is characterized by the presence of Sb in the inclusions, which was not observed in any other sample of copper alloys or silver alloys.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations